PP459 Healthcare Resource Utilisation Of Anti-Neutrophil Cytoplasmic Antibody Associated Vasculitis Patients: Real-World Data From English Clinical Practice Research Datalink. (December 2020) - de Arellano Serna, Antonio Ramirez; Glover, Matt; Sammon, Cormac; Kuo, Tzu-Chun; Spearpoint, Philip; Rutherford, Peter
Abstract : Introduction: Anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) is a rare, serious and often life-threatening disease. The use of available treatments options (immunosuppressants and glucocorticoids (GCs)) improves the prognosis of AAV greatly; however, GC use is associated with significant toxicity related morbidities and the management of AAV is costly. However, information of the costs associated with AAV in the United Kingdom is limited. This study aimed to quantify the burden of AAV using a large England and Wales source of real-world data, the Clinical Practice Research Datalink (CPRD) Hospital Episode Statistics (HES) linked database, to identify healthcare resource utilization and generate estimates of costs. Methods: Incident patients (n = 220) were included if ≥ eighteen years, with diagnosis read codes G754.00/G75A.00; ICD codes M31.3/M31.7 from January 1997 to December 2017. Costs were taken from Unit Costs of Social and Health Care, National Health Service reference costs and electronic drug tariff. Distinction was made between type of consultations, outpatient visits and inpatient admission based on Healthcare Resource Grouping. Costs were summarised as mean per member per year (PMPY) in 2016 prices and presented before and after diagnosis. Results: In the year preceding AAV diagnosis, mean costs PMPY were GBP12, 012 [USD15, 400], (GBP5, 339 [USD6, 845] inpatient, GBP766 [USD982] outpatient, GBP314 [USD403] GP, GBP5, 594 [USD7, 172] GP prescribing). In the year of AAV diagnosis (Y0) costs PMPY were GBP28, 252 [USD36, 220], GBP15, 436 [USD19, 790] inpatient, GBP1, 863 [USD2, 388] outpatient, GBP2, 407 [USD3, 086] GBP8, 545 [USD10, 956] GP prescribing). Costs in the years post-diagnosis remained higher than pre-diagnosis with a low of GBP22, 839 [USD29, 281] in Y4. The prescribing costs (GC, methotrexate and azathioprine) were the largest contributor in Y0-Y4 (GBP15, 047 [USD19, 291] Y1; GBP12, 325 [USD15, 801] Y4). Conclusions: Diagnosis of AAV is associated with increased healthcare costs, including higher inpatients costs in the year of diagnosis and subsequently higher prescribing costs in the community. Given the incidence (17.2 cases per million) and considering only costs in the year of diagnosis, an additional GBP15.6 million [USD24.6 million] of healthcare resource utilization occurs every year from new diagnoses of AAV. However, this will likely be underestimated due to the lack of secondary care prescribing data in CPRD-HES and prescribing of immunosuppressant treatments in this setting.